Rapid genotyping of inversion variants in Mucopolysaccharidosis type II using long-range PCR: A case report - Yusuke Hattori; Jun Kido; Keishin Sugawara; Takaaki Sawada; Shirou Matsumoto; Kimitoshi Nakamura (Molecular Genetics and Metabolism Reports, 2024)
Mucopolysaccharidosis II (MPS II) is a lysosomal storage disease caused by a deficiency in iduronate-2-sulfatase (IDS), leading to the accumulation of dermatan sulfate and heparan sulfate in lysosomes. Traditionally, genotyping of the IDS gene has been conducted through exome sequencing, which fails to detect inversion variants. Consequently, when no pathogenic variants are detected in exons, additional PCR-based analysis is required. Herein, we introduce a rapid genotyping technique method using long-range PCR for MPS II patients. We successfully identified an inversion variant and confirmed the sequences of the inversion regions. We also confirmed that the pathogenic variant in the patient originated de novo. These findings suggest that long-range PCR genotyping can identify inversion variants more rapidly compared to the previous PCR-based methods, making it a valuable tool for newborn screening (NBS) and genetic diagnosis.